2008
DOI: 10.1002/joc.1794
|View full text |Cite
|
Sign up to set email alerts
|

The return period of wind storms over Europe

Abstract: Accurate assessment of the magnitude and frequency of extreme wind speed is of fundamental importance for many safety, engineering and reinsurance applications. We utilize the spatial and temporal consistency of the European Centre for Medium Range Forecasts ERA-40 reanalysis data to determine the frequency of extreme winds associated with wind storms over the eastern North Atlantic and Europe. Two parameters are investigated: 10-m wind gust and 10-m wind speed. The analysis follows two different view-points: … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
116
0
2

Year Published

2010
2010
2016
2016

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 136 publications
(127 citation statements)
references
References 62 publications
(80 reference statements)
4
116
0
2
Order By: Relevance
“…For instance, Pfahl and Wernli (2012a) found a good correspondence between the timing of precipitation extremes in ERA-Interim and in the CMORPH satellite data set (see Joyce et al, 2004). Della-Marta et al (2009) analysed the representation of 200 severe European wind storms compiled from different observational sources in the ERA40 reanalysis, the predecessor of ERA-Interim. They found problems in the reanalysis wind gust data only in regions with high surface roughness, which were caused by a parameterisation issue that has been eliminated in ERA-Interim (cf.…”
Section: Extreme Eventsmentioning
confidence: 98%
See 1 more Smart Citation
“…For instance, Pfahl and Wernli (2012a) found a good correspondence between the timing of precipitation extremes in ERA-Interim and in the CMORPH satellite data set (see Joyce et al, 2004). Della-Marta et al (2009) analysed the representation of 200 severe European wind storms compiled from different observational sources in the ERA40 reanalysis, the predecessor of ERA-Interim. They found problems in the reanalysis wind gust data only in regions with high surface roughness, which were caused by a parameterisation issue that has been eliminated in ERA-Interim (cf.…”
Section: Extreme Eventsmentioning
confidence: 98%
“…Dee et al, 2011). An advantage of using wind data from reanalysis is the improved temporal homogeneity compared to many measurement time series (Della-Marta et al, 2009;Pfahl et al, 2009). …”
Section: Extreme Eventsmentioning
confidence: 99%
“…While using instantaneous values created the possibility of aliasing of the maximum wind field, whereby a storm front moved more than one grid box in six hours, this was preferable to using the six-hourly maximum 10 m gust, which is problematic in areas of high surface roughness (Della-Marta et al, 2009).…”
Section: The Historical Storm Setmentioning
confidence: 99%
“…Many similar SSIs have been used previously in the literature (Della-Marta et al, 2009;Donat et al, 2010;Leckebusch et al, 2008) as well as in defining financial contracts based on parameters of observed or modelled wind speed (usually referred to as "Catastrophe Bonds"). Our SSI is similar to that of Leckebusch et al (2008) who used cubed wind speeds normalised by a local quantile.…”
Section: The Historical Storm Setmentioning
confidence: 99%
“…Extreme value theory (EVT) is widely used in climatology to estimate return periods of extreme events (van den Brink et al, 2005;Della-Marta et al, 2009) and in conjunction with risk assessment. It is also applied to homogenise climate data (Della-Marta and Wanner, 2006).…”
Section: Introductionmentioning
confidence: 99%